Effects of Sihuang Zhili Granules on the Diarrhea Symptoms, Immunity, and Antioxidant Capacity of Poultry Challenged with Lipopolysaccharide (LPS) - Shaolong Wang; Chong Li; Chaosheng Zhang; Guohua Liu; Aijuan Zheng; Kai Qiu; Wenhuan Chang; Zhimin Chen (MDPI AG, 2023)
A growing interest has been focused on Chinese herbs as alternatives to antimicrobial growth promoters, which are characterized by non-toxic side effects and drug resistance. The purpose of this study was to evaluate the effects of the Sihuang Zhili granule (abbreviated as Sihuang) on diarrhea, immunity, and antioxidation in poultry. Thirty male Leghorn chickens, aged 21 days, were randomly assigned to one of three groups with ten animals each. The control group (CON) received intraperitoneal saline injections, while the LPS-challenged group (LPS) and Sihuang intervention group (SH) received intraperitoneal injections of LPS (0.5 mg/kg of BW) and Sihuang (5 g/kg) at d 31, d 33, d 35, respectively. The control and LPS groups were fed a basal diet, while the SH group was fed a diet supplemented with Sihuang from d 21 to d 35. Analysis of the diarrhea index showed that the addition of Sihuang inhibited the increase in the diarrhea grade and the fecal water content caused by LPS, effectively alleviating poultry diarrhea symptoms. The results of the immune and antioxidant indexes showed that Sihuang significantly reduced the contents of the pro-inflammatory factors TNF- α and IL-1 β, as well as the oxidative stress markers ROS and MDA. Conversely, it increased the contents of the anti-inflammatory factors IL-4 and IL-10, along with the activities of antioxidant enzymes GSH-Px and CAT, thereby enhancing the immune and antioxidant abilities of chickens. Furthermore, Sihuang protected the chicken's ileum, liver, and immune organs from LPS invasion and maintained their normal development. In conclusion, this study confirmed the antidiarrheal effect of Sihuang in poultry farming and demonstrated its ability to improve poultry immunity and antioxidant capacity by modulating antioxidant enzyme activity and inflammatory cytokine levels.